Vascularized Thoracodorsal to Suprascapular Nerve Transfer, a Novel Technique to Restore Shoulder Function in Partial Brachial Plexopathy - Potter, Shirley M.; Ferris, Scott I. (Frontiers in Surgery, 2016)
We describe the clinical outcome of a novel nerve transfer to restore active shoulder motion in upper brachial plexus injury. The thoracodorsal nerve was successfully used as a vascularized donor nerve to neurotize to the suprascapular nerve in a patient with limited donor nerve availability. At four years follow-up, he had regained useful external rotation of the injured limb, with no significant donor site morbidity. Shoulder abduction return was less impressive however, and reasons for this are discussed. We provide a comprehensive review of the literature on this topic and a subsequent discussion on the details of this novel technique. This is the first reported case of thoracodorsal nerve to suprascapular nerve transfer, and also the first reported case of a vascularized thoracodorsal nerve transfer in the English language literature. We advocate direct thoracodorsal to suprascapular nerve transfer as a valid surgical option for the restoration of shoulder function in patients with partial brachial plexus avulsion, when conventional nerve donors are unavailable.